2011
DOI: 10.4103/0253-7176.92067
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Adverse Drug Reactions of Atypical Antipsychotic Drugs in Psychiatry OPD

Abstract: Background:Novel atypical antipsychotics are superior to conventional antipsychotics as they significantly reduce both positive and negative symptoms of schizophrenia and have lower risk of extrapyramidal symptoms (EPS). However, these drugs have separate set of adverse drug reactions (ADRs). Therefore, this study was carried out to assess these ADRs, which can have impact on long-term compliance and achieving successful treatment.Materials and Methods:A prospective study of analysis of ADR of atypical antipsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 14 publications
2
29
0
Order By: Relevance
“…1 Most common ADRs produced by olanzapine in the present study was weight gain, increased appetite and diabetes mellitus, similar to study conducted by Shah et al, Sengupta et al and Kiran et al 1,3,12 Haloperidol produced maximum extrapyramidal symptoms similar to study conducted by Taruna et al 4 Extrapyramidal symptoms can impair quality of life, stigmatise patients and lead to poor antipsychotic adherence and relapse.…”
Section: Discussionsupporting
confidence: 86%
“…1 Most common ADRs produced by olanzapine in the present study was weight gain, increased appetite and diabetes mellitus, similar to study conducted by Shah et al, Sengupta et al and Kiran et al 1,3,12 Haloperidol produced maximum extrapyramidal symptoms similar to study conducted by Taruna et al 4 Extrapyramidal symptoms can impair quality of life, stigmatise patients and lead to poor antipsychotic adherence and relapse.…”
Section: Discussionsupporting
confidence: 86%
“…The demographic details of the present analysis showed male gender predominance over females w.r.t ADRs, which was similar to the findings of some other studies. 16,17 Several other studies have found that ADRs are more common in females than in males. 18,19 However, another study showed no difference in the occurrence of ADRs in male and female patients 20 showing thereby that the influence of gender may be incidental only and have no influence on the number of ADRs reported.…”
Section: Discussionmentioning
confidence: 97%
“…Olanzapine most commonly involved in weight gain while risperidone caused extrapyramidal symptoms that are in line with the previous study. 29 One Indian study observed olanzapine and haloperidol as most common offending drugs among psychiatric outpatients. 30 The difference for common antipsychotics may be due to the difference in utilization pattern of drugs.…”
mentioning
confidence: 99%